Islamic Education In The Millennial Era:Efforts To Realize The Excellent Generation - Mohammad Al Farabi (Proceeding International Seminar of Islamic Studies, 2019)
The millennial era that is ongoing today is a phase of life that is destined for generations born when technology and the internet have developed rapidly. They are known for a generation that is not only comfortable with technology, but also feels uncomfortable living without technology. Advances in technology on the one hand are recognized to make it easier for students to find information and knowledge, but on the other hand it also causes a shift in values in the attitude of life and practice of religion as a bias towards freedom and hyper technology. In responding to these conditions, Islamic education must be involved by making various strategic efforts to change the challenges faced in order to become an opportunity as an effort to give birth to a Excellent generation who is intelligent and has good character.This article will explain the important role of Islamic education to be responsible in the midst of the changing times that put forward the use of digital technology as a medium of communication and learning resources. Through the use of library research methods, this article collects various ideas, facts, research results and opinions from experts accompanied by related analysis, so it is seen how important the contribution of Islamic education is in creating a Excellent generation that has not only intellectual and material potential, but also potentially, morally and spiritually.